1970
DOI: 10.3758/bf03335656
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prey movement and background on predatory behavior of chameleons

Abstract: Four small populations of American chameleons (Anolis carolinensis) were tested to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1971
1971
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Rather, the usual pattern is that reptiles and amphibians are bom with stimulus predispositions that control the release of phylogenetically preorganized feeding responses (see Burghardt, 1966;Burghardt & Abeshaheen, 1971;Fuchs & Burghardt, 1971;Herzog & Burghardt, 1974). SUBOSKI Unlearned releasers may 00 general stimulus characteristics of environmental objects such as size and movement (Askew et al, 1970;Burghardt, 1964Burghardt, , 1969Herzog & Burghardt, 1974;Ingle, 1968). Unlearned releasers may also 00, as has been widely demonstrated for snakes, specific stimulus characteristics such as chemosensory features of particular prey species.…”
Section: Learned Recognitiod Of Foodmentioning
confidence: 99%
“…Rather, the usual pattern is that reptiles and amphibians are bom with stimulus predispositions that control the release of phylogenetically preorganized feeding responses (see Burghardt, 1966;Burghardt & Abeshaheen, 1971;Fuchs & Burghardt, 1971;Herzog & Burghardt, 1974). SUBOSKI Unlearned releasers may 00 general stimulus characteristics of environmental objects such as size and movement (Askew et al, 1970;Burghardt, 1964Burghardt, , 1969Herzog & Burghardt, 1974;Ingle, 1968). Unlearned releasers may also 00, as has been widely demonstrated for snakes, specific stimulus characteristics such as chemosensory features of particular prey species.…”
Section: Learned Recognitiod Of Foodmentioning
confidence: 99%
“…Several authors have stressed the importance of visual stimuli on predatory behavior in lizards belonging to other families. In general, visual cues appear to be important in locating prey and orienting predatory attacks in three-dimensional space (Cooper, 1981), in prey discrimination and selection (Askew, Musimeci, Sloane, & Stephan, 1970;Brockhusen-Holzer & Curio, 1990;Burghardt, 1964;Díaz & Carrascal, 1993;Kaufman et al, 1996;Reznick, Sexton, & Mantis, 1981), and in rejection of distasteful prey (Boyden, 1976;Hasegawa & Taniguchi, 1994;Sexton, 1964).…”
Section: The Role Of Visual and Chemical Prey Cues In Predatory Behaviormentioning
confidence: 99%
“…Because previous studies have shown that both visual and olfactory cues are important in the foraging behavior of brown treesnakes, we attempted to incorporate visual and odor cues into the construction of an artificial lure to increase its effectiveness relative to the use of chemical cues alone. The importance of the visual aspects of movement on prey selection in snakes (Burghardt, 1966;Smith and Watson, 1972;Herzog and Burghardt, 1974) and lizards (Askew et al, 1970;Gluesing, 1983;Kaufman et al, 1996) is well known. Predators generally orient to moving versus nonmoving prey.…”
mentioning
confidence: 99%